Mercury concentration in fish and shellfish in Kuwait - Sara Al Qabandy; Abdullatif Aloumi; Fajer Al Enezi; Mohammad E. Al Mukaimi; Robert J. Hoffman (Toxicology Communications)
Mercury is a metal pollutant found in water, soil, and air. Mercury serves no physiological purpose in humans and it is strictly a toxin with dose-dependent adverse health effects. As seafood is a major component of the Kuwaiti diet, we sought to evaluate seafood locally caught in Kuwait, including fish and shellfish, to measure its mercury concentration. Our purpose was to determine and describe the average mercury concentration in various Kuwaiti seafoods, and determining if these concentrations exceed the US Food and Drug Administration (FDA) recommended safe limits for consumption. In this study, approximately half of the samples tested in Kuwait contained mercury concentrations that exceeded US FDA recommended safe limits. Further investigations and ongoing monitoring of mercury in seafood of Kuwait would be prudent.